Clinical Significance of a Negative Loop Electrosurgical Excision Procedure Biopsy in Patients With Biopsy-Confirmed High-Grade Cervical Intraepithelial Neoplasia. Issue 2 (April 2015) - Nam, Kyehyun; Ryu, Aeli; Jeon, Seob; Kim, Jeongsig; Kwak, Jeongja; Park, Bora
<x xml:space="preserve">Abstract</x> Objective We sought to determine which clinical factors can predict this phenomenon and to better understand the clinical significance of negative loop electrosurgical excision procedure (LEEP) findings through long-term follow-up. Methods We identified 559 patients with biopsy-confirmed cervical intraepithelial neoplasia grade 2 or 3 (CIN 2, 3) who were treated by LEEP between February 2001 and December 2010. Preconization clinical characteristics, as well as high-risk human papillomavirus (hrHPV) status, were analyzed as possible predictors of an absence of a lesion in the specimen. The clinical significance of an absence of a lesion in the specimen, as well as other factors, was evaluated by Cox hazard regression analysis in terms of recurrence. Results No lesion on the LEEP specimen was found in 102 (18.2%) of 559 patients with CIN 2, 3 on punch biopsy. Punch biopsy status of CIN 2, low HPV viral load (<100 relative light units [RLU]), and negative or positive HPV infection other than type 16 were significantly related to no lesion in the LEEP specimen. Postoperative HPV persistence (≥10 RLU) and same-type HPV detection were significantly related to recurrent disease of CIN 2+ (p < .001). The recurrence of patients with no lesion in LEEP did not statistically differ from that of patients with a lesion in the LEEP specimen (p = .390). Conclusions The absence of a lesion in the LEEP specimen is very common. A negative LEEP is associated with a persistence/recurrence rate similar to that of positive LEEP. We recommend that the follow-up for patients with no lesion in the LEEP specimen should be the same as that for patients with a lesion.